2011
DOI: 10.9753/icce.v32.management.36
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Coastal Protection Scheme for Ada at the Volta-River Mouth (Ghana)

Abstract: The coastal town Ada in Ghana is threaded by a severe coastal erosion. A protection scheme has to be designed to protect the town. Since the area is ecologically important, e.a. due to the presence of turtles, both during the design process and during the construction phase actions to diminish possible negative effects have to be considered. The design is supported by measuring campaigns and numerical modeling of the currents, waves and morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Runoff before dam construction was about 87.5 mm/yr, compared to the post-dam period value of 73.5 mm/yr (Oguntunde et al 2006). Since the construction of the dam, there are no longer any pronounced peaks in flow discharge and the sediment transport is reduced to only 10% of the original transport rate (Bollen et al 2011;Boateng et al 2012). The reduced sediment supply to the delta system has affected the evolution of the delta (Appeaning Addo et al 2018), shifting from a sediment-dominated towards a more wave-dominated delta (Roest 2018).…”
Section: The Volta Deltamentioning
confidence: 89%
See 1 more Smart Citation
“…Runoff before dam construction was about 87.5 mm/yr, compared to the post-dam period value of 73.5 mm/yr (Oguntunde et al 2006). Since the construction of the dam, there are no longer any pronounced peaks in flow discharge and the sediment transport is reduced to only 10% of the original transport rate (Bollen et al 2011;Boateng et al 2012). The reduced sediment supply to the delta system has affected the evolution of the delta (Appeaning Addo et al 2018), shifting from a sediment-dominated towards a more wave-dominated delta (Roest 2018).…”
Section: The Volta Deltamentioning
confidence: 89%
“…Coastal erosion in the Volta Delta was first reported in 1929, but is posited to have existed since at least the 1860s, particularly in Keta (Nairn et al 1999). Ly (1980) estimated that the shoreline in Keta was eroding at a rate between 4 and 8 m/yr, while Bollen et al (2011) reported that the shoreline in Totope-Ada is receding at a rate of about 6 m/yr. Kumapley (1989) estimated that a strip of coastal land about 1 km wide has been lost to erosion since 1880s.…”
Section: The Volta Deltamentioning
confidence: 99%
“…The yearly sediment transport before the dam construction was about 7.5 million m 3 /s (Bollen et al, 2011). Since the construction of the dam, there are no peaks in flow discharge, and the sediment transport is reduced to only a fraction of the original transport (Bollen et al, 2011).…”
Section: Catchment and Sediment Supplymentioning
confidence: 99%
“…The yearly sediment transport before the dam construction was about 7.5 million m 3 /s (Bollen et al, 2011). Since the construction of the dam, there are no peaks in flow discharge, and the sediment transport is reduced to only a fraction of the original transport (Bollen et al, 2011). This dramatic reduction in sediment supply to the delta system has affected the evolution of the delta and resulted in significant shoreline recession (Allersma and Tilmans, 1993;Armah, 1991).…”
Section: Catchment and Sediment Supplymentioning
confidence: 99%
See 1 more Smart Citation